Azobisisobutyronitrile loaded on mesoporous silica particles: A new stressor for solid-state oxidative forced degradation studies - Petřík, Jakub; Zůza, David; Heřt, Jakub; Řezanka, Pavel; Krejčík, Lukáš; Hrubcová, Kateřina; Štěpánek, František (Journal of pharmaceutical and biomedical analysis, 2023)
A new approach for testing drug sensitivity to autooxidative degradation in the solid state is demonstrated in this work. A novel solid-state form of stressing agent for autooxidation has been proposed, based on azobisisobutyronitrile loaded into mesoporous silica carrier particles. The new solid-state form of the stressing agent was applied in degradation studies of two active pharmaceutical ingredients: bisoprolol and abiraterone acetate. The effectiveness and predictivity of the method were evaluated by comparing impurity profiles with those obtained by traditional stability testing of commercial tablets containing the investigated APIs. The results obtained by the new solid-state stressor were also compared with those obtained by an existing method for testing peroxide oxidative degradation in the solid state using a complex of polyvinylpyrrolidone with hydrogen peroxide. It was found that the new silica particle-based stressor was able to effectively predict which impurities could be formed by autooxidation in tablets and that this new approach is complementary to methods for testing peroxide oxidative degradation known from the literature.
Keywords: oxid křemičitý; peroxidy; Oxidative stress testing; Oxidative Stress; Peroxides; Mesoporous silica; Impurity profile; Silicon Dioxide; Bisoprolol fumarate; Abiraterone acetate; oxidační stres; Tablets; Solid-state degradation; tablety